Penilaian Tingkat Kecemasan Pasien Program Rujuk Balik di Fasilitas Kesehatan Tingkat Pertama Kota Malang - Permata, Agung; Fitri, Aldesra; Abdullah, Muhammad Rizal; Salmasfattah, Novyananda (Sainstech Farma: Jurnal Ilmu Kefarmasian, 2023)
Referral Program Services (PRB) are health services provided to patients in health facilities based on referrals from specialist doctors or sub-specialists who treat these patients. This study aims to look at the characteristics and assess the level of anxiety of the Referral Patient Program at the First Level Health Facility in Malang City. Anxiety level assessment used the Generalized anxiety disorder-7 (GAD-7) questionnaire. This type of research is analytic observational with cross sectional design. The sampling technique was carried out using the convenience sample method. The sample of this study were Patients of the Referral Program (PRB) at First Level Health Facilities in Malang City, to be precise in the outpatient unit during May 2023 who met the inclusive and exclusion criteria. The data collected was analyzed descriptively according to the number of categories for each variable and determined the level of anxiety using the GAD-7 questionnaire to obtain an overview of the data in the form of frequency and proportion (%). The results of the study showed that there were 37 (37%) males and 63 (63%) females, the highest age was >60, namely 36 patients (36%), the highest diagnosis of hypertension was 58 patients (58%), last education the highest was at the senior high school level, namely 42 patients (42%), in the employment status of the highest DRR patients, namely not working, 51 patients (51%), in marital status, 100 patients were married (100%), and the highest monthly income was <Rp. 2,500,000 ie 66 patients (66%). The anxiety level of PRB patients at FKTP Malang City obtained the highest level of anxiety at the mild anxiety level (48%) and the lowest at the severe anxiety level (2%).